Mechanical Properties of Ecological Concrete Made with Steel Slag and Seashells: A Systematic Literature Review - Huamani Sánchez, Saul Andrés; Salcedo Apaza, Helard Gustavo; Márquez, Gerson José (LACCEI, 2025)
Concrete is an essential material in construction worldwide, but its production generates a high carbon footprint. A promising strategy to reduce this environmental impact is the development of sustainable concretes by replacing conventional aggregates with natural waste or industrial by-products. This Systematic Literature Review analyses the effect of steel slag and seashells on the mechanical properties of concrete. The literature search, based on the PICO methodology, found 2384 sources in the Scopus, EBSCOhost and Scilit databases. After applying eligibility criteria according to the PRISMA statement, 62 relevant articles were selected. The results show that steel slag is mainly used in ultra-high performance concretes, while seashells are more frequent in cellular concretes. Chemical analysis indicates that iron oxide (Fe2O3) is the predominant component in steel slag, while calcium carbonate (CaCO3) predominates in seashells. The incorporation of steel slag significantly improves the mechanical strength and durability of concrete, while seashells contribute to improving its mechanical properties and reducing the risk of cracking. In conclusion, although the benefits of steel slag in green concretes are well documented, further research is required on the potential of seashells and the synergistic effect of both wastes in the manufacture of sustainable concretes.